Neural correlates of aesthetic tragedy: evidence for enhanced semantic processing and cognitive control in response to tragic versus joyful music - Li, Chia-Wei; Tsai, Chen-Gia (Frontiers in Psychology, 2025)
Philosophers and psychologists have long examined the paradox of negative emotions in art, yet its neural underpinnings remain insufficiently understood. This study employed functional magnetic resonance imaging to compare neural responses to the opening phrases of major- and minor-mode musical themes during the recapitulation section of first-movement sonata form. Compared to the major mode, the minor mode is generally associated with more negative emotional connotations. When presented with relatively greater loudness and a vigorous tempo, minor-mode themes often convey a sense of tragic force. Whole-brain analysis revealed significantly greater activation in the bilateral middle temporal gyrus (MTG), right lateral frontal pole (LFP), and right angular gyrus for tragic (minor-mode) compared to joyful (major-mode) themes. Elevated MTG activation suggests increased semantic processing demands involved in the construction of socio-affective meaning in response to tragic themes, whereas enhanced LFP activation likely reflects the engagement of high-level cognitive control and emotion regulation mechanisms. Complementary qualitative analyses of participants’ written responses further indicated that tragic themes more frequently elicited imagery of external oppression and internal emotional turmoil or uncertainty—patterns not observed for joyful themes. These findings provide neuroscientific support for the Distancing–Embracing model of the enjoyment of negative emotions in art reception.